Keragaan Morfologi Salak (Salacca zalacca (Gaertn.) Voss) Di Provinsi Bengkulu - Lalan Darham Daulay; Rustikawati; Catur Herison (University of Prof. Dr. Hazairin, SH, 2026)
Snake fruit (Salacca zalacca (Gaertn) is a tropical fruit crop that is widely favored by consumers and possesses high economic value. To increase snake fruit production in Bengkulu Province, plant breeding efforts are required to develop superior, location-specific cultivars. Morphological characterization is essential for identifying genotype characteristics that can serve as plant descriptors and facilitate the selection of desirable traits. This study aimed to evaluate the genetic diversity and morphological performance of snake fruit genotypes in Bengkulu Province, Indonesia. Twelve snake fruit genotypes were observed, namely Bali, Pondoh, Condet, Sinase, Lumut, Manggis, Gula Pasir, Hutan, Gading, Manon Jaya, Madu, and Banjarnegara. A total of 27 morphological characters were evaluated. Quantitative data were analyzed using the Student’s t-test. The results revealed considerable morphological variation among the evaluated genotypes. Based on fruit cluster yield components, including the number of fruits per cluster and the number of clusters per plant, genotypes S7 (Gula Pasir) and S8 (Hutan) showed the greatest potential for high economic value. Meanwhile, genotype S6 (Manggis) exhibited superior fruit quality traits, including fruit flesh weight, edible portion, and flesh thickness. These findings indicate the existence of substantial genetic variability among snake fruit genotypes in Bengkulu and provide valuable information for future breeding and selection programs aimed at developing high-yielding and superior-quality cultivars.